Effect of positive and negative dimensions of mental imagery and self-talk on learning of soccer kicking skill - Lotfi, G.; Tahmasbi, F.; Forghani, M. H.; Szwarc, A. (Physical Education of Students, 2020)
Background and Study Aim. Mental imagery and self-talk are two important mental skills that are used for improvement of performance and learning of motor and sport skills. This study aimed to investigate the effect of positive/negative mental imagery and positive/negative self-talk on learning of soccer kicking skill. Material and Methods. Participants included 48 young soccer player students. Participants were soccer player students with mean age 18.44 and SD=.88 years. After selecting the sample and filling out the personal detail form, the imagery and self-talk instructions, the method of completing mental imagery questionnaire, Moore-Christine kick-skill test instructions, and principles of free kick at soccer were explained to participants. Then, the mental imagery test and kick-skill test were run in 4 blocks of 4 attempts and the results were recorded. Based on their pre-test scores, the participants were divided into 4 groups. The acquisition sessions were held for 3 weeks and 2 sessions per week, with 8 blocks of 4 trials (32 trials) per session. The data was analyzed using one-way ANOVA, mixed ANOVA, and two-way ANOVA tests at different learning stages (significance level= 0.05). Results. The results of data analysis showed that positive imagery and positive self-talk groups performed significantly better than negative imagery and negative self-talk groups. Also, due to the significance of interactive effect of imagery × training sessions, it was found that the positive imagery groups performed significantly better than negative imagery groups from the third session onwards. Conclusion. According to the results, it was recommended that trainers use this aspect of self-talk at early stages of training. Also, the positive imagery can be emphasized by increasing the training sessions in more skilled individual.